1996
DOI: 10.1029/96jd00932
|View full text |Cite
|
Sign up to set email alerts
|

An extended data set of river discharges for validation of general circulation models

Abstract: Using existing measurements of streamflow data, we present a new data set of fiver discharges to the ocean, for use in validating climate models. This data set includes annual mean discharges for 981 rivers, representing approximately 824,500 m3/s of global river discharge. This is about 65% of contemporary estimates of continental precipitation minus continental evaporation (P-E). Using our new data set, we present a self-consistent water budget over continents. We find that rivers with annual mean discharges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 11 publications
7
87
0
Order By: Relevance
“…13. Distribution of river runoff (as fraction of total runoff, coloured boxes), as calculated from Perry et al (1996) for rivers south of 60…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13. Distribution of river runoff (as fraction of total runoff, coloured boxes), as calculated from Perry et al (1996) for rivers south of 60…”
Section: Discussionmentioning
confidence: 99%
“…To account for mass preservation on long timescales, we re-supply it again via river runoff, using a subset of river runoff data of Table 2 of Perry et al (1996), i.e., the volumetric flow rates of the largest rivers in the world. We did not use direct P-or N-discharge rates, because these may exhibit a strong anthropogenic influence, e.g., due to fertilizers, and therefore may not correspond to the steady-state system envisaged here.…”
Section: Phosphorus Budget Closure Via River Runoffmentioning
confidence: 99%
“…The productivity in the eastern basin is fueled not only by coastal upwelling (Signorini et al, 1999) but also by dust deposition off the West African coast (Mills et al, 2004). Moreover, nutrient input by major tropical rivers such as the Senegal, Gambia and Niger (Perry et al, 1996) contribute to enhanced production off the West African coast, indicated by enhanced chlorophyll a concentrations (for the 2002 seasonal cycle of chlorophyll a see monthly data set of Sea-viewing Wide Field-of-view Sensor (SeaWiFS): http://earthobservatory.nasa.gov/Observatory/Datasets/ chlor.seawifs.html).…”
Section: N 2 O In the Surface Layer Of The North Atlanticmentioning
confidence: 99%
“…So, according to Poulos et al [4] the mean annual value is 158 m 3 /s whereas this parameter was estimated to be 135 or 146 m 3 /s in Ref. [9].…”
Section: Ecorad 2001mentioning
confidence: 99%
“…Using this estimate and mean annual discharge one could estimate mean turbidity as 5.8 kg/m 3 (6.8 kg/m 3 using discharge data from [9]). Data on surface contamination by radio-caesium for the Greek territory of the Axios watershed are available in the "Atlas" [10] whereas no published data for FYROM territory were found.…”
Section: Ecorad 2001mentioning
confidence: 99%